The Golden Anniversary of Mass Incarceration in America - Lurigio, Arthur J. (The prison journal, 2024)
The year 2023 marked the 50th anniversary of mass incarceration in the United States. For six decades, the U.S. incarceration rate has been near the top among all countries worldwide. In five major sections, this article offers a brief retrospective on mass incarceration. The first defines the nature of prison sentences. The second describes the current prison population's characteristics. The third examines the growth of the prison population, highlighting politically motivated policies and laws. The fourth provides a reckoning of the collateral damage caused by mass incarceration. The fifth and final section considers strategies to reduce imprisonment and its attendant harms.